Attitudes of Nursing and Medical Students towards Patient Care on Psychiatric Ward During Clinical Rotation at Mbarara Regional Referral Hospital. - Namulema, Angella (Student’s Journal of Health Research Africa, 2021)
Introduction: During psychiatry, clinical rotation, nursing, and medical students care for mentally ill patients who have abnormal thoughts, behaviors, perceptions, and relationships with others is very important. This makes patient care on the psychiatric ward very special and the attitudes towards patient care on the ward very key to providing quality care. Study purpose: This study sought to explore the attitudes of nursing and medical students towards patient care in the psychiatric ward during clinical rotation. Methodology: A qualitative descriptive design was employed. The study involved 9 fourth-year nursing students and 4 fifth and 2 fourth-year medical students who were selected by purposive sampling. Data were collected using face-to-face semi-structured in-depth interviews and analyzed using thematic analysis. Results: Three themes emerged from 12 categories describing attitudes of nursing and medical students towards patient care on the psychiatric ward during clinical rotation. The emergent themes were positive attitudes, negative attitudes, and uncertainty of attitudes. Conclusion: In conclusion, these qualitative findings suggest that nursing and medical students held both positive and negative attitudes towards patient care on the psychiatric ward during clinical rotation. In some participants the attitudes were uncertain.